Last-male sperm precedence in Rhynchophorus ferrugineus (Olivier): observations in laboratory mating experiments with irradiated males. Issue 1 (3rd October 2017) - Musmeci, S.; Belvedere, S.; Sasso, R.; Arnone, S.; Cristofaro, M.; Nobili, P.; La Marca, A.; De Biase, A.
Abstract: The Red Palm Weevil (RPW) Rhynchophorus ferrugineus (Olivier 1790) is an invasive pest from southeastern Asia and Melanesia that in the last 30 years has spread widely in the Middle East and Mediterranean Basin. Its stem-boring larvae cause great damage to several palm species of the Arecaceae family, many of which are economically important for agricultural and ornamental purposes. Therefore, great attention has recently been focused in studying this species to identify sustainable and effective eradication strategies, such as sterile insect technique (SIT). The rapid spread of RPW is associated with its high reproductive success. To evaluate the suitability of a SIT strategy, particular physiological and behavioral aspects of RPW reproduction, such as the presence of polyandry and post-copulatory sperm selection mechanisms, were investigated. To determine paternity of progeny from multiply mated females, double-crossing experiments were carried out confining individual females with either a wild-type male or a γ-irradiated male (Co-60). Fecundity and fertility of females were scored to evaluate post-copulatory sperm selection. Results showed that progeny were almost exclusively produced by the sperm of the second male, suggesting that a last-male sperm precedence is expressed at high levels in this species, and providing interesting insights for an area-wide RPW management strategy such as the SIT.